Utility of a screening test (MoCa) to predict amyloid physiopathology in mild cognitive impairment (2020)
Introduction: The MoCa (Montreal Cognitive Assessment) Screening test has become relevant in recent years in the screening of patients with Mild Cognitive Impairment (MCI). It is important to seek and study simple and reliable tools in clinical practices that correlate with biological markers that have been used to predict conversion from MCI to AD. Objective: To analyze the MOCA and its cognitive sub-scores and the relationship with Amyloid pathophysiology in Alzheimer’s Disease. Methodology: 32 patients with MCI were studied, they were separated according positive (n: 20) and negative (n: 12) underlying amyloid pathology. The patients performed a extensive cognitive assessment that included MoCa Test. Results: MoCa Total Scores showed significantly different results between groups (p < 0.001) and the Orientation Score (MoCa OIS)) (p < 0.05) with worse performance of patients with amyloid pathophysiology. Score of MoCa a cut-off point of < 24 was established, since the diagnostic sensitivity at this point was 83% and the specificity 70%. Conclusions: The MoCa is a useful tool to differentiate biomarker status in MCI. Future studies should study this tool in the prodromal phases of the disease.